HCV viraemia associates with NK cell activation and dysfunction in antiretroviral therapy‐treated HIV/HCV‐co‐infected subjects. Issue 10 (11th May 2017) - Papasavvas, E.; Azzoni, L.; Yin, X.; Liu, Q.; Joseph, J.; Mackiewicz, A.; Ross, B.; Lynn, K. M.; Jacobson, J. M.; Mounzer, K.; Kostman, J. R.; Montaner, L. J.
Summary: The impact of hepatitis C virus (HCV) RNA levels on immune status in chronically HCV mono‐infected when compared to HIV/HCV co‐infected on antiretroviral therapy (ART) remains poorly understood. A total of 78 African American subjects HCV viraemic/naïve to HCV treatment (33 HCV genotype 1 mono‐infected, 45 ART‐treated HIV/HCV genotype 1 co‐infected) were studied. Clinical and liver enzyme measurements were performed. Whole blood was analysed for immune subset changes by flow cytometry. Peripheral blood mononuclear cells (PBMC) were used for same‐day constitutive and in vitro Interferon (IFN)‐α‐induced signal transducer and activator of transcription (STAT) phosphorylation, K562 target cell lysis and K562 target cell recognition‐mediated IFN‐γ production. Statistical analysis was performed using R (2.5.1) or JMP Pro 11. While both groups did not differ in the level of liver enzymes, HIV/HCV had higher T‐cell activation/exhaustion, and constitutive STAT‐1 phosphorylation compared to HCV. In contrast, CD4 + FoxP3 + CD25 + frequency, IFN‐αR expression on NK cells, as well as constitutive and IFN‐α‐induced direct cytotoxicity were lower in HIV/HCV. Linear regression models further supported these results. Finally, increase in HCV viral load and CD4 + T‐cell count had an opposite effect between the two groups on NK cell activity and T‐cell activation, respectively. HCV viral load in ART‐treated HIV/HCV co‐infection was associated with greater immune activation/exhaustion and NK dysfunction than HCV viral load alone in HCV mono‐infection. The more pronounced immune modulation noted in ART‐treated HIV‐co‐infected/untreated HCV viraemic subjects may impact HCV disease progression and/or response to immunotherapy.